Inflammatory joint disease and human immunodeficiency virus infection. Issue 6637 (11th June 1988) - Forster, S M; Seifert, M H; Keat, A C; Rowe, I F; Thomas, B J; Taylor-Robinson, D; Pinching, A J; Harris, J R W
Abstract : Nine men positive for antibody to human immunodeficiency virus (HIV) who developed peripheral, non-erosive arthritis were followed up. The clinical features were compatible with reactive arthritis but were atypical in several respects: the joint symptoms were generally severe, persistent, and unresponsive to non-steroidal anti-inflammatory drugs. The onset of arthritis was associated with various infections, none of which are known to be associated with the development of reactive arthritis. HLA typing was performed for three patients, all of whom were positive for HLA-B27. HIV was isolated from the synovial fluid of one patient. No patient had AIDS before developing arthritis, but four progressed to having AIDS after a mean of 7·5 months, and two died. Arthritis resolved in only one patient. The possibility of HIV infection should be considered in all patients with conditions suggesting reactive arthritis. Synovitis in patients with severe immunodeficiency has important pathogenetic implications.